2021
DOI: 10.1080/14992027.2021.1933620
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the social challenges and emotional distress associated with hearing loss: a qualitative investigation using Leventhal’s self-regulation theory

Abstract: Objective: To explore the lived experience of social challenges and emotional distress in relation to hearing loss and the coping mechanisms employed to manage them.Design: Two focus groups and two one-on-one semi-structured interviews were conducted during February 2020. Transcripts were first inductively analysed to identify experiential that use of strategies that interfere with or inhibit effective communication (such as social avoidance) are associated with an increased risk of hearing aid rejection (Helv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
(56 reference statements)
1
35
0
Order By: Relevance
“…In 12 studies liminality (i.e., the threshold of conscious awareness) was suggested to constrain whether a listening-related skill was perceivable by adults with HL (and therefore accessible for insight) and that liminal thresholds varied across skills and across individuals [ 43 , 45 , 46 , 49 , 52 , 58 , 59 , 61 , 70 73 ]. The contributing studies suggested that listening skills may be further classified as having an auditory-linguistic focus (28 studies) [ 39 , 40 , 43 , 45 47 , 49 51 , 56 , 57 , 59 , 60 , 62 65 , 69 72 , 74 79 ], or a compensatory focus (28 studies) [ 39 , 41 43 , 45 49 , 51 , 52 , 54 , 56 60 , 62 70 , 75 ]. Auditory-linguistic skills included skills relating to components of auditory or linguistic processing (e.g., listening to high frequency sounds, ability to listen to multiple speakers, utilising of semantic knowledge); whereas compensatory skills were suggested to be skills/actions deployed by an adults with HL to offset the suboptimal auditory signal arising from HL and/or the current acoustic conditions (e.g., planning, use of visual clues such as written text).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 12 studies liminality (i.e., the threshold of conscious awareness) was suggested to constrain whether a listening-related skill was perceivable by adults with HL (and therefore accessible for insight) and that liminal thresholds varied across skills and across individuals [ 43 , 45 , 46 , 49 , 52 , 58 , 59 , 61 , 70 73 ]. The contributing studies suggested that listening skills may be further classified as having an auditory-linguistic focus (28 studies) [ 39 , 40 , 43 , 45 47 , 49 51 , 56 , 57 , 59 , 60 , 62 65 , 69 72 , 74 79 ], or a compensatory focus (28 studies) [ 39 , 41 43 , 45 49 , 51 , 52 , 54 , 56 60 , 62 70 , 75 ]. Auditory-linguistic skills included skills relating to components of auditory or linguistic processing (e.g., listening to high frequency sounds, ability to listen to multiple speakers, utilising of semantic knowledge); whereas compensatory skills were suggested to be skills/actions deployed by an adults with HL to offset the suboptimal auditory signal arising from HL and/or the current acoustic conditions (e.g., planning, use of visual clues such as written text).…”
Section: Resultsmentioning
confidence: 99%
“…Listening behaviours and skills were described as either having an orientation towards self (25 studies), such adjusting one’s proximity to the speaker [ 39 45 , 49 , 51 , 52 , 56 59 , 61 , 62 , 64 67 , 69 , 70 , 75 , 78 , 80 ], or an orientation towards others (19 studies) [ 39 , 41 , 43 , 45 , 48 50 , 54 , 56 , 58 60 , 62 , 64 66 , 68 , 81 ]. For example, adults with HL described asking their communication partners to adapt their behaviour to facilitate interaction [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Audiologists or social healthcare workers are encouraged to provide emotional support and address the psychosocial needs for individuals with hearing loss, which might be helpful to improve mental health [ 52 , 53 ]. However, despite the existing need by individuals with hearing loss, to date healthcare services for hearing-impaired individuals are mainly focused on treatment [ 54 ] and psychosocial support is rarely provided to them for coping with the social difficulties related to hearing loss [ 55 ]. This calls for effective interventions to tackle the issues related to increasing prevalence and detrimental impact of both social isolation and hearing loss.…”
Section: Discussionmentioning
confidence: 99%